THE EFFECT OF COLLABORATIVE ASSESSMENT AND LEARNING STYLE ON STUDENTSâ WRITING COMPETENCY - Subawa, IM; Nitiasih, N.P.K.; Putra, I.N.A. (International Journal of Language and Literature, 2017)
This experiment study aims at investigating the effect of collaborative assessment and learning style on studentsâ writing competency of eleventh grade students of SMAN 1 Kuta. To conduct this research, 92 students were selected as the sample. The design of this research was 2x2 factorial design. Data of writing competency were collected by an instrument called posttest which is essay type test, meanwhile learning style data were collected by questionnaire. The acquired data were analyzed statistically by two way ANOVA and Tukey test. This research discovers: 1) there is a significant effect of collaborative assessment on studentsâ writing competency, 2) there is a significant interaction effect of assessment type (collaborative and conventional assessments) and learning style (field dependent and independent) on studentsâ writing competency, 3) collaborative assessment affects significantly on field dependent studentsâ writing competency, and 4) collaborative assessment does not affect significantly on field independent studentsâ writing competency.